Oxalate Crystallization under the Action of Brown Rot Fungi - Dmitry Yu. Vlasov; Marina S. Zelenskaya; Alina R. Izatulina; Svetlana Yu. Janson; Olga V. Frank-Kamenetskaya (Crystals, 2023)
Brown rot fungi belong to the wood-rotting fungi, which produce oxalic acid and actively decompose wood. We first found oxalates formed under the action of brown rot fungi in natural conditions on stone (Rogoselga adit, Karelia, Russia), proposed a model for their formation, and confirmed the hypothesis that frequent occurrence of metal oxalates in mines and adits may be associated with the activity of these fungi. We synthesized under the action of four species of brown-rot fungi (Serpula himantioides, Serpula lacrymans, Coniophora puteana, Antrodia xantha) on different mineral substrates analogs of all known biofilm oxalate minerals and oxalates of such toxic heavy metals as Pb, Cu, Mn. In addition, we compared the features of oxalate formation under the action of brown rot fungi and soil fungus Aspergillus niger, an active oxalic acid producer, widely used in model experiments and recommended for application in biotechnologies. It is shown that in contrast to A.niger, the contribution of the metabolic activity of brown rot fungi to oxalate crystallization exceeds the contribution of the underlying minerals. The prospects for the use of brown rot fungi such as Serpula himantioides, Coniophora puteana, and Antrodia xantha in modern environmentally friendly biotechnologies are justified.